Interaction of Vasopressin with Human Blood Platelets: Dependency on Mg2+ - Roos, Isabella; Ferracin, Fabrizia; Pletscher, Alfred (Thrombosis and Haemostasis, 1986)
Arginine-vasopressin (AVP) in the presence of Mg2+ but not in the absence of bivalent cations led to accumulation of [32P]-phosphatidic acid ([32P]-PA) in human blood platelets. Mg2+ also enhanced the specific binding of [3H]-AVP to intact platelets. The concentrations of the cation which enabled AVP to cause half maximal rise of [32P]-PA and those inducing half maximal [3H]-AVP-binding were of the same order. It is concluded that the stimulation of phosphatidyl inositide breakdown by AVP in presence of Mg2+ is at least partially due to a Mg2+-induced enhancement of specific AVP-binding to the platelet membranes.
Keywords: Blood platelets of man; Arginine-vasopressin; Phos-phoinositide turnover: dependence on Mg2+; Magnesium ions; Vasopressin binding: dependence on Mg2+